Effect of freezing and thawing on ejaculated sperm and subsequent pregnancy and neonatal outcomes in IVF - Xie, Qin; Jiang, Xueyi; Zhao, Ming; Xie, Yating; Fan, Yong; Suo, Lun; Kuang, Yanping (Frontiers in Endocrinology, 2024)
Background Techniques for sperm cryopreservation have exhibited their potential in male fertility preservation. The use of frozen–thawed sperm in in vitro fertilization (IVF) cycles is widespread today. However, many studies reported that cryopreservation might have adverse effects on sperm DNA integrity, motility, and fertilization, probably due to cold shock, intra- and extracellular ice crystals, and excess reactive oxygen species (ROS). Studies suggested that freezing and thawing impaired sperm viability and might adversely affect subsequent fertilization and pregnancy outcomes. The potential damage to fertilization and subsequent embryonic development and offspring health raises the concern on sperm cryopreservation. However, the above mentioned studies are limited to intracytoplasmic sperm injection (ICSI) cycles, while IVF is a more natural and patient-friendly method. IVF requires a higher quality of sperm than ICSI. However, the effect of freezing and thawing on sperm used for IVF remains unknown. Therefore, we aim to investigate the effect of freezing and thawing on ejaculated sperm and subsequent pregnancy and neonatal outcomes in IVF. Methods This retrospective cohort study at a tertiary-care academic medical center included 447 women who used paternal frozen–thawed ejaculated sperm and 31,039 women who used paternal freshly ejaculated sperm for IVF and underwent frozen–thawed blastocyst transfer from January 2011 to September 2021. To balance the baseline characteristics of the two groups, patients using frozen sperm were matched with control groups using a propensity score matching algorithm with a ratio of 1:3. Results Although sperm motility decreased from 82.04% to 75.70% (P < 0.001) after the freezing–thawing process, the fertilization rate (68.27% for frozen sperm and 67.54% for fresh sperm), number of viable embryos (1.98 and 2.16), clinical pregnancy rate (44.7% and 51.8%), and live birth rate (40.3% and 42.4%) were comparable between the two groups (all P > 0.05). For neonatal outcomes, no between-group differences were observed in offspring gender, gestational age, birthweight, and the rate of preterm birth (21.7% and 12.9%), low birthweight neonates (19.2% and 16.0%), and birth defects (0.0% and 0.8%) (all P>0.05). Conclusions Frozen–thawed sperm had lower sperm motility but resulted in comparable embryonic, pregnancy, and neonatal outcomes versus fresh sperm in IVF cycles.